Copper(ii) phthalocyanine supported on a three-dimensional nitrogen-doped graphene/PEDOT-PSS nanocomposite as a highly selective and sensitive sensor for ammonia detection at room temperature1. Issue 97 (21st October 2015) - Dehsari, Hamed Sharifi; Gavgani, Jaber Nasrollah; Hasani, Amirhossein; Mahyari, Mojtaba; Shalamzari, Elham Khodabakhshi; Salehi, Alireza; Taromi, Farmarz Afshar
<x xml:space="preserve">Abstract</x> A novel CuTSPc@3D-(N)GF/PEDOT-PSS nanocomposite gas sensor allowed excellent sensitivity and selectivity for NH3 at room temperature.